Dilated Cardiomyopathy Several Months after Hemolytic Uremic Syndrome - Esfandiar, Nasrin; Alaei, Fariba; Sharifian, Mostafa; Alaei, Mastaneh; Dalirani, Reza; Khalilian, Mohammad Reza (Journal of Pediatric Nephrology, 2016)
This is a report of a 44-month-old baby girl diagnosed as a case of atypical hemolytic uremic syndrome (aHUS) presenting with hematuria, periorbital edema, anemia, thrombocytopenia, and hypertension lacking any history of previous bloody diarrhea. She was treated with plasma infusion followed by plasmapheresis and peritoneal dialysis. After two months, she was discharged in remission undergoing periodic plasmapheresis. Four months later, she was visited for fatigue, tachypnea, and palpitation. Cardiac evaluation revealed dilated cardiomyopathy with an ejection fraction of 15-20%. She was hospitalized and treated with inotropes and diuretics; one week later, she was discharged in a favorable condition. After six months follow-up, she showed an acceptable renal and cardiac state. It seems that cardiomyopathy can occur as a late and rare complication of HUS. We recommend cardiac evaluation for all patients with HUS at its presentation and in later follow-ups. Keywords: Cardiomyopathy; Hemolytic Uremic Syndrome; Child.